The importance of human milk donation in the contribution of development to premature newborns (Research, Society and Development, 2021)
Introduction: The human milk bank aims to develop a reflection on the need to donate human milk to premature newborns, in order to promote the primordial, protective and developmental food for their life. Objective: To describe the way to donate breast milk while in prenatal care and to inform the importance of health education addressing breastfeeding and the route for donation. Methodology: This is an integrative review research, with a qualitative approach of a basic nature and exploratory objective, which was based on data from the Virtual Health Library Nursing using the Health Sciences Descriptors (DeCS): Milk bank; Maternal nutrition; Donation of milk. After searching with the descriptors, full articles were selected, in Portuguese, published between 2016 and 2021. Based on the criteria obtained, we reached 13 articles that dealt with the proposed theme for the construction of the study.Results: The study shows data obtained that pointed out the need for safety and improvement of LH, data in which, they must be transcribed with found findings, in order to reach the objective of this study. Final Considerations: Nurses' performance is essential, being extremely important for the creation of a bond in view of the difficulties faced by nursing mothers to know the milk bank and encourage its use, aiming at the health education of these women and the professional growth of nurses in the face of theme.